[Symphonic Band Award from California Assembly] (1975)
William V. Johnson, Jeff Clark (Student Band President), Assemblyman Robert Nimmo, Douglas Pickard' This may be the receiving of Resolution 229 by the California Assembly Rules Committee commending the Cal Poly Symphonic Band in 1975 (See Cal Poly Report from June 24, 1975).